KAIDAH FIKIH DALAM LEGITIMASI PUTUSAN DISPENSASI KAWIN: (KAJIAN PUTUSAN PENGADILAN AGAMA DI KALIMANTAN SELATAN) - Zaidah, yusna zaidah; Abdul Hamid; Erma Sauva Asvia (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Abstract:The principles of Islamic Jurisprudence are frequently employed by courts to legitimize marriage dispensation cases involving prospective brides and grooms who have not yet reached the legal minimum age for marriage, thereby allowing them to marry legally. This study is motivated by the perception that courts tend to readily approve such dispensations by referencing the principles of Islamic Jurisprudence as a primary legal consideration. Judges often cite "very urgent reasons" based on the emotional closeness and duration of the relationship between the two prospective brides and grooms. However, trial findings reveal that many of these relationships lasted only two to four months. This discrepancy prompts a deeper analysis of the judges’ reasoning and the appropriateness of applying the principles of Islamic Jurisprudence in each case. This research adopts a normative legal approach with a case study method, focusing on the legal reasoning employed by judges in granting marriage dispensations. The findings indicate that the primary justification offered by judges is the emotional bond between the young couples, along with concerns about potential immoral behaviour if marriage is delayed. The Islamic Jurisprudence principles—particularly those addressing considerations of public benefit (maslahah) and potential harm (mafsadah)—are used to support such rulings. However, the application of these principles in several cases appears inconsistent with the actual legal facts presented during the trial.   Keywords: Islamic Jurisprudence Principles, Marriage Dispensation, Legal Consideration